New multienzymatic complex formed between human cathepsin D and snake venom phospholipase A2 - Moraes, Jeane do Nascimento; Francisco, Aleff Ferreira [UNESP]; Dill, Leandro Moreira; Diniz, Rafaela Souza; de Oliveira, Claudia Siqueira; da Silva, Tainara Maiane Rodrigues; Caldeira, Cleópatra Alves da Silva; Corrêa, Edailson de Alcântara; Coutinho-Neto, Antônio; Zanchi, Fernando Berton; Fontes, Marcos Roberto de Mattos [UNESP]; Soares, Andreimar Martins; et al. (FapUNIFESP (SciELO), 2022)
Background: Cathepsin D (CatD) is a lysosomal proteolytic enzyme expressed in almost all tissues and organs. This protease is a multifunctional enzyme responsible for essential biological processes such as cell cycle regulation, differentiation, migration, tissue remodeling, neuronal growth, ovulation, and apoptosis. The overexpression and hypersecretion of CatD have been correlated with cancer aggressiveness and tumor progression, stimulating cancer cell proliferation, fibroblast growth, and angiogenesis. In addition, some studies report its participation in neurodegenerative diseases and inflammatory processes. In this regard, the search for new inhibitors from natural products could be an alternative against the harmful effects of this enzyme. Methods: An investigation was carried out to analyze CatD interaction with snake venom toxins in an attempt to find inhibitory molecules. Interestingly, human CatD shows the ability to bind strongly to snake venom phospholipases A2 (svPLA2), forming a stable muti-enzymatic complex that maintains the catalytic activity of both CatD and PLA2. In addition, this complex remains active even under exposure to the specific inhibitor pepstatin A. Furthermore, the complex formation between CatD and svPLA2 was evidenced by surface plasmon resonance (SPR), two-dimensional electrophoresis, enzymatic assays, and extensive molecular docking and dynamics techniques. Conclusion: The present study suggests the versatility of human CatD and svPLA2, showing that these enzymes can form a fully functional new enzymatic complex.
Keywords: Cathepsin D; Enzyme complex; Phospholipases A2; Snake venom